Establishment and evaluation of a prognostic model for sodium overload necrosis in acute myeloid leukemia - Xie, Kunying; Wei, Jin (Translational Cancer Research, 2026)
Acute myeloid leukemia (AML) is a highly heterogeneous hematologic malignancy with a poor prognosis. Recent studies have revealed that sodium overload-induced necrosis participates in the pathogenesis of various tumors; however, its role in AML remains unclear. In this study, we developed a risk model based on genes related to sodium overload-induced necrosis to predict survival outcomes in patients with AML.